The Application of a Multidisciplinary Framework for Optimizing the Monitoring System for Geological CO2 Storage - Yngve Heggelund; Martha Lien; Danny Otto (C, 2025)
The technical objective of a monitoring system is to provide the means to detect potential irregularities related to the project plan, to provide assurance that the migration of the CO2 plume stays within the storage unit, and to show that CO2 behaves in conformance with the model predictions. From an operational point of view, monitoring will also provide data that can be used to optimize the injection schedule relative to the storage capacity and availability of CO2 to minimize risks and long-term costs. Finally, monitoring is a crucial factor for the public perception of risks related to CO2 storage, as surveys indicate that adequately designed monitoring can mitigate concerns. The Analytical Hierarchy Process (AHP) is a holistic, transdisciplinary, multi-criteria decision-making framework. The objective of this work is to apply the AHP framework to monitoring-solutions for a synthetic geological storage site of CO2 to secure the technical, operational, and societal embeddedness of the solutions and gain experience in how this can be applied to a real project. Through this first application of AHP within the field of geological carbon storage, the AHP was found to be a structured and transparent framework for holistic, multi-criteria decision-making (MCDM), where the wisdom and expertise of different domain experts were considered. A further novelty in this study is introducing a measure of spread in assessing the various solution alternatives’ capacity to meet monitoring criteria. This approach was utilized to underscore disparities among respondents’ experiences and to identify potential informational deficiencies in evaluating alternatives and devising the optimal monitoring solution.